High cryptic diversity across the global range of the migratory planktonic copepods Pleuromamma piseki and P. gracilis. - Kristin M K Halbert; Erica Goetze; David B Carlon (PLoS ONE, 2013)
Although holoplankton are ocean drifters and exhibit high dispersal potential, a number of studies on single species are finding highly divergent genetic clades. These cryptic species complexes are important to discover and describe, as identification of common marine species is fundamental to understanding ecosystem dynamics. Here we investigate the global diversity within Pleuromamma piseki and P. gracilis, two dominant members of the migratory zooplankton assemblage in subtropical and tropical waters worldwide. Using DNA sequence data from the mitochondrial gene cytochrome c oxidase subunit II (mtCOII) from 522 specimens collected across the Pacific, Atlantic and Indian Oceans, we discover twelve well-resolved genetically distinct clades in this species complex (Bayesian posterior probabilities >0.7; 6.3-17% genetic divergence between clades). The morphologically described species P. piseki and P. gracilis did not form monophyletic groups, rather they were distributed throughout the phylogeny and sometimes co-occurred within well-resolved clades: this result suggests that morphological characters currently used for taxonomic identification of P. gracilis and P. piseki may be inaccurate as indicators of species' boundaries. Cryptic clades within the species complex ranged from being common to rare, and from cosmopolitan to highly restricted in distribution across the global ocean. These novel lineages appear to be ecologically divergent, with distinct biogeographic distributions across varied pelagic habitats. We hypothesize that these mtDNA lineages are distinct species and suggest that resolving their systematic status is important, given the ecological significance of the genus Pleuromamma in subtropical-tropical waters worldwide.